Inkjet-printed SnOx as an effective electron transport layer for planar perovskite solar cells and the effect of Cu doping - Dongli Lu; Feipeng Yang; Chaochao Dun; Jinghua Guo; Jeffrey J. Urban; Liubov Belova (Royal Society Open Science, 2024)
Inkjet printing is a more sustainable and scalable fabrication method than spin coating for producing perovskite solar cells (PSCs). Although spin-coated SnO2 has been intensively studied as an effective electron transport layer (ETL) for PSCs, inkjet-printed SnO2 ETLs have not been widely reported. Here, we fabricated inkjet-printed, solution-processed SnOx ETLs for planar PSCs. A champion efficiency of 17.55% was achieved for the cell using a low-temperature processed SnOx ETL. The low-temperature SnOx exhibited an amorphous structure and outperformed high-temperature crystalline SnO2. The improved performance was attributed to enhanced charge extraction and transport and suppressed charge recombination at ETL/perovskite interfaces, which originated from enhanced electrical and optical properties of SnOx, improved perovskite film quality, and well-matched energy level alignment between the SnOx ETL and the perovskite layer. Furthermore, SnOx was doped with Cu. Cu doping increased surface oxygen defects and upshifted energy levels of SnOx, leading to reduced device performance. A tunable hysteresis was observed for PSCs with Cu-doped SnOx ETLs, decreasing at first and turning into inverted hysteresis afterwards with increasing Cu doping level. This tunable hysteresis was related to the interplay between charge/ion accumulation and recombination at ETL/perovskite interfaces in the case of electron extraction barriers.